Komunikasi Interelasi Antarummat Beragama Dalam Kehidupan Masyarakat Plural - Asriadi Asriadi (Institut Agama Islam Negeri Kendari, 2022)
Interrelation between religious communities is a challenge faced by the world's religions today. All religions tend to have a claim to absolutism, be it Islam, Christianity, Hinduism or Judaism. The particularistic-subjective claims of adherents of monotheism will have an impact on inter-religious conflicts. The differences between religions are only at the level of exotericism, while at the level of esotericism there is a meeting point. We cannot ignore the differences that exist within each religion to draw the conclusion that “all must be one”. In understanding the issue of religions, it is necessary to have a multicultural approach, where this approach tries to keep away from absolute, subjective and exclusive attitudes that put forward the moral and social aspects of religion.